Atomic structure [filem jalur] (Fairfield, Conn. : Communication Skills Corp., 1974)
Contents : 1. Electron configurations and orbital diagrams -- 2. Atomic structure and the periodic table : an introudction -- 3.Electrical forces within atoms -- 4. Classification of the elements : metals, non-metals